2016
DOI: 10.2522/ptj.20160089
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Pain for Patients Seeking Physical Therapy: Can Functional Magnetic Resonance Imaging (fMRI) Help?

Abstract: In the multidisciplinary fields of pain medicine and rehabilitation, advancing techniques such as functional magnetic resonance imaging (fMRI) are used to enhance our understanding of the pain experience. Given that such measures, in some circles, are expected to help us understand the brain in pain, future research in pain measurement is undeniably rich with possibility. However, pain remains intensely personal and represents a multifaceted experience, unique to each individual; no single measure in isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Pain is acknowledged to be as much a psychological phenomenon as physiological; wherein, a complex integration of multiple physiological, and cognitive/emotional processes, as well as sociocultural exposures, are shaped by individual context, past experiences, perceived sense of self, and one's expectation for recovery. 104 Over the last 2 decades, brain neuroimaging has resulted in a shift towards characterizing the neural processing of a patient's pain experience and how we consider the effect of pain, or the experience thereof, 34 on the brain itself. 83 fMRI has demonstrated that nociceptive processing and the subjective perception of pain is not encoded by a single brain region but distributed across a network of multiple brain regions, each with specific roles in the sensory and affective dimensions of the pain experience.…”
Section: Brain Imagingmentioning
confidence: 99%
“…Pain is acknowledged to be as much a psychological phenomenon as physiological; wherein, a complex integration of multiple physiological, and cognitive/emotional processes, as well as sociocultural exposures, are shaped by individual context, past experiences, perceived sense of self, and one's expectation for recovery. 104 Over the last 2 decades, brain neuroimaging has resulted in a shift towards characterizing the neural processing of a patient's pain experience and how we consider the effect of pain, or the experience thereof, 34 on the brain itself. 83 fMRI has demonstrated that nociceptive processing and the subjective perception of pain is not encoded by a single brain region but distributed across a network of multiple brain regions, each with specific roles in the sensory and affective dimensions of the pain experience.…”
Section: Brain Imagingmentioning
confidence: 99%
“…Few investigators report using even simple but critical methodological controls such as co-registration and how the slices were aligned in plane to reduce noise, and discrepant findings from repeated measures [91]. We argue a way forward is to explore and develop consensus-driven standardized measurement approaches similar to what has been proposed for measuring the structure and composition of lumbar paravertebral muscles [92] and for quantifying the patient’s pain experience using functional magnetic resonance imaging [93].…”
Section: Muscle Fat Infiltration As a Biological Marker Of Diseasementioning
confidence: 99%